If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying y + 2 = 23(x + -9) Reorder the terms: 2 + y = 23(x + -9) Reorder the terms: 2 + y = 23(-9 + x) 2 + y = (-9 * 23 + x * 23) 2 + y = (-207 + 23x) Solving 2 + y = -207 + 23x Solving for variable 'y'. Move all terms containing y to the left, all other terms to the right. Add '-2' to each side of the equation. 2 + -2 + y = -207 + -2 + 23x Combine like terms: 2 + -2 = 0 0 + y = -207 + -2 + 23x y = -207 + -2 + 23x Combine like terms: -207 + -2 = -209 y = -209 + 23x Simplifying y = -209 + 23x
| Y=10c | | t=(x-1)(1-x) | | 8/3y=5/6x-2 | | 20log(x)=-12 | | -62=1-9w | | -39-2x=7x-6(1+7x) | | X^2+6x=59 | | 8v=2(4v+-2) | | -3x+50=2x+10 | | -12=-2(x+5) | | In(2x)=-2 | | 4-7x+6x=0 | | t=(x-7)(2+y) | | 9m=6(a+4) | | -19=2+4(h+7) | | 754/1000000 | | 3x(2x-3)=27 | | 17j-6=14j+7 | | 18.24=-16t^2+24t+8 | | 3n-9=2n+13 | | 8-6n=-7+5(5n+3) | | 7i/8i | | -8x+y=50 | | x-12/5=-6 | | 7-(2-y)=-4 | | 18.24=-16t+24t+8 | | x+39-3x-40=949 | | 9*45=5(f-32) | | (n-12)*8=80 | | x+x+37+4x-40=819 | | 19-5x=7x+19 | | -3y-27=-6(y+6) |